Enjeux et conflits autour de la terre urbaine. Politiques foncières et planification urbaine en Colombie - Alice Beuf (Cahiers des Amériques Latines)
Colombia adopted one of the law of land and urban development –law of “urban renewal”– the most innovative and regulationists in Latin America. Perceived as ambitious in its goals and planning and land management tools that in its grants municipalities, the Law 388 of 1997 is a decline of the 1991 Constitution in the urban field. But the application of this law is facing strong resistance, in part related to divergent conceptions of property right. The article analyses the implementation of this new model of urban planning and management of urban land, its effects in big Colombian cities, as well as developments in the application of the statutory instruments relating to the conflicting interests of urban actors: national government, municipalities, formal and informal agents of production of urban spaces, residents committees.